Plastic Responses of Gilthead Seabream Sparus aurata to Wild and Aquaculture Pressured Environments - Talijančić, Igor; Žužul, Iva; Kiridžija, Viktorija; Šiljić, Jasna; Pleadin, Jelka; Grubišić, Leon; Šegvić-Bubić, Tanja (Frontiers in Marine Science, 2021)
Fish farms, as artificial marine structures with a constant food supply, have a high capacity to attract surrounding wild fish. Different phenotypes of abundant gilthead seabream have been recorded in natural and aquaculture pressured environments in the eastern Adriatic Sea, where the influence of tuna farming on plastic traits associated with habitat use and foraging behaviour remains largely unknown. Several traits, such as body and otolith shape, external colouration, diet preference, and proximate tissue content, were analysed to examine habitat selection of the tuna farm-associated phenotype in comparison to wild and farmed phenotypes. Foraging behavioural shifts in prey selectivity, from hard-shelled bivalves towards soft textured baitfish feed, and local hydrodynamic conditions have initiated plastic responses in farm-associated seabream. Consequently, morphological traits connected with feeding and swimming performance and paler vs. vivid body colouration patterns differed between wild and farm-associated fish, highlighting the existence of resource polymorphism in gilthead seabream. While otolith shape proved to be a reliable phenotypic tracer in distinguishing farmed from wild and farm-associated fish, reduced sensitivity was found between individuals residing in the vicinity of tuna farms and wild ones. To fully understand the impact of fish farms on associated gilthead seabream and its plastic response with a distinctive morph outcome, the underlying molecular mechanisms involved in the regulation of alternative phenotypes needs to be investigated.